2016
DOI: 10.1371/journal.pone.0149513
|View full text |Cite
|
Sign up to set email alerts
|

Serum TGF-β1 as a Biomarker for Type 2 Diabetic Nephropathy: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundAbnormal expression of serum TGF-β1 was found in patients with diabetic nephropathy. However, the association of TGF-β1 with the risk of diabetic nephropathy remains unknown. The present study was undertaken to investigate whether such an association exists.MethodsWe searched the Chinese VIP, Wangfang, China National Knowledge Infrastructure, PubMed, Embase, and Google Scholar databases for relevant studies and extracted all eligible data. Stata12 software was used for statistical analysis.ResultsNin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Consistent with a previous report [50], the penile cross-sectional area (%) was decreased in DM mice, resulting in atrophy of the penis. The increase of collagen fibers in the testis of animals with DM 72 Day A may have been caused by increased expression of transforming growth factor beta 1 and nitric oxide synthase [51][52][53][54]. Similar to our study, previous studies have demonstrated decreases of sperm concentration in DM human and animal models [5,6,37,42,[55][56][57][58], which may be due to impaired spermatogenesis [5,6,12,57,[59][60][61].…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with a previous report [50], the penile cross-sectional area (%) was decreased in DM mice, resulting in atrophy of the penis. The increase of collagen fibers in the testis of animals with DM 72 Day A may have been caused by increased expression of transforming growth factor beta 1 and nitric oxide synthase [51][52][53][54]. Similar to our study, previous studies have demonstrated decreases of sperm concentration in DM human and animal models [5,6,37,42,[55][56][57][58], which may be due to impaired spermatogenesis [5,6,12,57,[59][60][61].…”
Section: Discussionsupporting
confidence: 85%
“…They reported that the levels of serum and urinary TGF-β1 were significantly increased in T2DM and T2DN. Mou et al [ 76 ] assessed 9 reports that included 264 patients and 227 healthy controls in a meta-analysis to study the relationship between serum TGF-β1 levels and the risk of diabetic nephropathy. Their study indicated that increased serum TGF-β1 levels in DM patients were associated with a high risk of renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression level of TGF-β1 has been treated as an indicator for the development of certain human diseases. In a recent study, Mou et al reported that serum levels of TGF-β1 levels were significantly higher in patients with diabetic nephropathy than those in healthy controls, and the increased TGF-β1 level in serum can be used to effectively distinguish diabetic nephropathy patients from people with normal physiological conditions [ 14 ]. In another study, increased serum TGF-β1 levels were proved to be responsible for the decreased chemotherapy response of non-small cell lung cancer cells, which is a major cause of unsatisfactory treatment outcomes and poor prognosis of those patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%